Creative Industry Development as a Local Economic Development Effort - Hasnidar Yuslin (Department of Islamic Economics, Islamic University of Indonesia, 2021)
The creative industry sector is quite mushrooming in Indonesia, one of which is in South Sulawesi Province right in Bone Regency, Awangpone District, Compong'e Village. This study aims to describe how the development of the creative industry as an effort to develop the local economy in DD songko' Recca. This research is descriptive qualitative with data collection techniques using observation and interviews. The findings show that the development of this creative industry can increase local economic development. The implications found it is hoped that the community, especially songko' recca craftsmen, in addition to this industry being used as local economic development, it is also hoped that in the manufacture of songko' recca still pay attention to the aesthetic values that have become the hallmark of this craft, and for the local government good communication is needed. as well as more attention by providing facilities and infrastructure in making songko' recca so that it can run effectively and efficiently. In addition, a work program in the relevant agencies is needed for the development of the creative industry, especially the manufacture of songko' recca. Keywords: creative industry, local economic development